Redescription and illustrations of the Centipede, Ectonocryptops kraepelini Crabill, 1977 (Scolopendromorpha: Scolopocryptopidae: Ectonocryptopinae) - Shelley, Rowland M.; Mercurio, Randy (Zootaxa, 2008)
In 1977, R. E. Crabill, Jr., erected Ectonocryptops for a new Mexican centipede from Colima that he named, E. kraepelini. He placed it in the Cryptopidae, but with 23 pairs of legs and pedal segments, it properly belongs in the Scolopocryptopidae, subfamily Ectonocryptopinae, according to today’s taxonomy (Shelley & Mercurio 2005). Crabill did not provide illustrations, and the holotype and only specimen, supposedly at the American Museum of Natural History, New York, USA (AMNH), was subsequently lost. Consequently, the identity of this centipede was uncertain until we (Shelley & Mercurio 2005) proposed Ectonocryptoides quadrimeropus, n. gen., n. sp., for an anatomically similar form from neighboring Jalisco. Discovery of the latter allowed us to interpret characterizations in Crabill’s verbal account of Ectonocryptops kraepelini, and separate generic status seemed warranted because of different numbers of podomeres on the caudal legs, four in Ectonocryptoides quadrimeropus and five in Ectonocryptops kraepelini (Crabill 1977). Repeated and extensive searches in the type and general collections at the AMNH failed to reveal the missing holotype as did ones at the National Museum of Natural History, Smithsonian Institution, Washington, DC, where Crabill was a curator when he described Ectonocryptops kraepelini. The holotype was discovered in the AMNH by the second author in 2005; the cephalic plate & antennae, coxosternum & segments 1–7, and segments 19–23 plus the caudal legs had been dissected, cleared, and mounted on a slide, whereas segments 8–18 were in a vial of alcohol. The slide mount was in extremely poor condition with darkened and cracked medium that was filled with air bubbles and meniscuses such that critical parts could not be clearly viewed. We removed the mounted parts from the slide, placed them in alcohol with the rest of the specimen, and redescribe Ectonocryptops kraepelini and provide, for the first time, illustrations of anatomical features. We also provide new accounts of the subfamily, Ectonocryptoides, and Ectonocryptoides quadrimeropus, so that all subfamilial components are treated in a single publication. Asterisks (*) in the account of Ectonocryptops kraepelini denote items taken from Crabill’s (1977) description that we could not confirm.